Issues in Transformation from Conventional Banking to Islamic Banking - Arshad, Muhammad Usman; Yusoff, Mohammed Effandi; Tahir, Muhammad Sohail (International Journal of Economics and Financial Issues, 2016)
The present era has witnessed intensive changes in last few decades. The transformation of conventional financial system to Islamic financial system is one of these drastic changes the world has faced. Islamic banking is the major constituent of the Islamic finance. In line with these transformations, Islamic banks and financial institutions are facing several problems due to non-existence of comprehensive framework. However, some prominent issues are convergence issues, stability and regulatory issues, existence of different schools of thought and sensitivity towards role of religion in commercial and financial sector. A careful analysis of these issues can lead to sort out the solutions. The approach to overcome these challenges will determine the future success or failure of the industry. Therefore, this study shed a light on some major challenges that can hinder the progress and benefits of Islamic finance promises. Keywords: Islamic Banks, Regulatory Framework, Financial Regulation, Governance, Financial Stability, Risk Management JEL Classifications: G21, G28, G32, O16, P15